The hidden power of illicit proof: a psychological approach - Iñiguez Ortiz, Eduardo (2017)
In the present article, the authors evaluate the psychological effects of the “illicit test”. To do this, they start delimiting their concept, and then analyze if it has any influence on the judge when resolving a case. Based on psychological considerations, in particular, the so-called “motivated reasoning” theory and the “motivated justice hypothesis”, they evaluate by an empirical study if the judges take this test into account when deciding, despite being legally bound to Not do it. In addition, they propose some mechanisms that could be used, both by litigants and by legal systems, to mitigate the effects of illicit veidence.